Evaluation of the Use of ChatGPT in Online Discussions: Its Impact on Student Understanding of Material and Interaction - Firdaus, Fadli; Syafrina, Mia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The rapid incorporation of artificial intelligence, notably ChatGPT, in online learning settings has raised questions about its impact on pedagogy. It is unclear whether AI use intensity inherently improves interaction quality and student pleasure or if other cognitive aspects like material knowledge are more important. This study analyzes two models—student interaction quality and student satisfaction—to assess ChatGPT's multifunctional role in online conversations. This quantitative study examines ChatGPT usage intensity, AI dependency, content understanding, interaction quality, and student happiness using structural models. The mechatronics program at Batam State Polytechnic collected data from students using AI techniques in online discussion forums. The findings indicated that the most consistent and dominant predictor of interaction quality and satisfaction is material understanding. ChatGPT intensity and content understanding promote interaction quality in Model 1, demonstrating its procedural support role. Model 2 demonstrates that student satisfaction is more influenced by material understanding and tool trust (dependence) than frequency of usage, suggesting that satisfaction is subjective and effective. The study reveals that AI integration alone does not guarantee success; pupils' cognitive competence and AI adaptation play a significant role. AI's procedural and affective effects on learning are distinguished in this educational technology study. It assists educators in positioning ChatGPT as a